Clinical, aetiological, and epidemiological studies of outpatient cases of hand, foot, and mouth disease in Chengdu, China, from 2019 to 2022: a retrospective study - Maoyao Xia; Yu Zhu; Juan Liao; Shirong Zhang; Denghui Yang; Peng Gong; Shihang Zhang; Guiyu Jiang; Yue Cheng; Jiantong Meng; Zhenhua Chen; Ye Liao; et al. (BMC Public Health)
Abstract Background The introduction of the Enterovirus A71 (EV-A71) vaccine in China in 2016 has led to a considerable decline in severe hand, foot, and mouth disease (HFMD) cases, with mild outpatient instances now representing the majority of HFMD cases in the country. Nevertheless, epidemiological investigations concerning mild outpatient cases remain scarce, resulting in inadequate descriptions of their clinical, etiological, and epidemiological characteristics. Our study aimed to analyze the clinical, etiological, and epidemiological characteristics of HFMD outpatients in Chengdu from 2019 to 2022 while identifying potential risk factors associated with the progression of outpatients requiring hospitalization. Methods A retrospective study was conducted to summarize the clinical, etiological, and epidemiological characteristics of outpatient HFMD cases in Chengdu from 2019 to 2022. Risk factors associated with progression to hospitalization of HFMD outpatients were evaluated using binomial logistic regression analysis. Results The study included 1,073 coxsackievirus A6 (CVA6), coxsackievirus A10 (CVA10), and coxsackievirus A16 (CVA16) HFMD nucleic acid test-positive outpatients. Among these, only 45 outpatients (4.19%) progressed to hospitalization. The median ages for CVA6, CVA10, and CVA16 infections were 25.23, 28.13, and 38.45 months, respectively (P < 0.001). CVA6 (76.51%, 821/1,073) has become the main serotype among outpatients in Chengdu, with the proportions from the second half of 2019 to 2022 being 45.59%, 95.17%, 77.67% and 80.71% respectively. EV-A71 cases even disappeared. Patients infected with CVA10 had a significantly higher likelihood of hospitalization (P < 0.05), while the presence of oral rash served as a protective factor (P < 0.05). Conclusions Our study highlights the critical need for enhanced surveillance of multiple HFMD pathogens, predominantly caused by the prevalent serotype CVA6. Clinically, enhanced surveillance of CVA10 is imperative to mitigate the hospitalization rate associated with HFMD.